Anti-dazzle coating liquid and optical film using same
By modifying high-refractive-index anti-glare particles and using ultraviolet curing technology, the wear problem of optical films under frequent touch and harsh environments has been solved, resulting in optical films with high anti-glare, low reflection, and high hardness, meeting the stringent requirements of displays.
Patent Information
- Application Number
- CN202511354984.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2025-11-28
AI Technical Summary
Existing optical films are prone to wear and tear and peeling under frequent touch and harsh environments, resulting in a decline in optical performance and failing to achieve both high hardness and anti-glare function.
Modified high-refractive-index anti-glare particles are used, including organic particles with silane coupling agents grafted with silicon carbide quantum dots. Combined with ultraviolet curing technology, a coating with a micro-rough structure and a reasonable refractive index difference is formed, avoiding structural defects introduced by hollow particles.
It achieves a high anti-glare rating (LV6) and low reflectivity (≤1%), while improving the hardness (pencil hardness ≥4H) and scratch resistance of the optical film to meet the needs of small-sized displays and touch displays.
Smart Images

Figure CN121022191A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optical film technology, specifically to an anti-glare coating liquid and an optical film using the same. Background Technology
[0002] Currently, display devices such as mobile phones, tablets, and automotive displays commonly use optical films with anti-glare (AG) and anti-reflection (AR) functions to improve visibility. The most mainstream technical solution is to construct a double-layer coating structure on a transparent substrate (such as PET, TAC, etc.). The first layer is the anti-glare layer (AG layer), which is adjacent to the transparent substrate and usually contains micron-sized organic or inorganic particles (such as acrylic resin particles, silica particles). The particles form a micro-rough surface in the coating to achieve light scattering, thereby achieving the anti-glare purpose. The second layer is the low refractive index layer (LR layer), which is placed on the AG layer and adjacent to the air interface. In order to achieve a sufficient refractive index difference (n) between the LR layer, the anti-glare layer, and the air, the LR layer is used. 空气 <n LR层 <n AG层 To satisfy the destructive interference condition of light, this layer typically requires the introduction of a low-refractive-index material, generally hollow silica nanoparticles. The hollow structure is filled with air (n≈1.0), which significantly reduces the effective refractive index of the LR layer, lowering it to an extremely low range of 1.25-1.35. Thus, as light passes sequentially through the air, LR layer, AG layer, and transparent substrate, it is reflected at multiple interfaces. By controlling the refractive index and thickness of each layer, the reflected light undergoes destructive interference, thereby reducing the overall reflectivity.
[0003] In optical films prepared using related technologies, the thin shells of hollow silica particles result in low mechanical strength. When a large number of hollow particles are introduced into the coating to reduce the refractive index, numerous pores and structural defects form within the coating, leading to a loose and non-dense overall structure. This results in low surface hardness, failing to achieve the hardness of a high-grade pencil and making the film easily scratched by hard objects. In daily use, such optical films cannot withstand repeated wiping or friction; the coating is prone to wear and peeling, leading to optical performance degradation and aesthetic damage. This contradiction between optical and mechanical properties severely limits the application of such optical films in environments requiring frequent touch and wiping, as well as harsh conditions (such as automotive and industrial equipment).
[0004] Therefore, there is an urgent need in this field for a new type of optical film that can maintain excellent low reflection and anti-glare functions, as well as high surface hardness and smoothness and excellent scratch resistance. Summary of the Invention
[0005] To solve the above-mentioned technical problems, this application can be implemented through the following technical solutions: This application provides an anti-glare coating liquid, comprising, by weight, 30 to 70 parts of a first main resin, 0.05 to 1 part of modified high-refractive-index anti-glare particles, 0.5 to 4 parts of a first photoinitiator, 30 to 70 parts of a first organic solvent, and 1 to 10 parts of a first auxiliary agent. The modified high-refractive-index anti-glare particles include organic particles with silicon carbide quantum dots grafted onto a silane coupling agent. The organic particles are polystyrene resin particles, poly(meth)acrylate resin particles, or poly(meth)acrylate-copoly-styrene copolymer resin particles.
[0006] As a further improvement to this application, the first main resin includes acrylate, methacrylate and its copolymers or homopolymers.
[0007] As a further improvement of this application, the first photoinitiator is selected from at least one of 1-hydroxycyclohexylphenyl ketone, benzyl dimethyl ketal, hydroxydimethyl acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin butyl ether.
[0008] As a further improvement of this application, the first organic solvent is selected from at least one of lower alcohols, acetates, ketones, cellosolves, dimethylformamide, tetrahydrofuran, propylene glycol monomethyl ether, toluene, and xylene having 1 to 6 carbon atoms.
[0009] As a further improvement of this application, the first additive is selected from at least one of dispersants, leveling agents, wetting agents, defoamers, antistatic agents, and leveling agents.
[0010] As a further improvement of this application, the modified high-refractive-index anti-glare particles are prepared by the following steps: A1. Preprocessing: Pretreatment of silicon carbide quantum dots: Add silicon carbide quantum dots to 30% concentrated nitric acid solution, mix thoroughly and evenly, then react at 50℃~100℃ for 1h~2h, wash until neutral, and dry to obtain hydroxylated silicon carbide quantum dots; Organic particle pretreatment: Add organic particles to ethyl acetate, mix thoroughly, then add toluene, mix thoroughly again to obtain an organic particle dispersion; A2. Coupling agent grafting: The silane coupling agent was dissolved in anhydrous ethanol, acetic acid was added, and after stirring thoroughly, the hydroxylated silicon carbide quantum dots obtained in step A1 were added. After stirring thoroughly and reacting, the mixture was washed by centrifugation with ethanol and dispersed in ethyl acetate to obtain a dispersion of silane coupling agent-grafted silicon carbide quantum dots in ethyl acetate. A3. Preparation of modified high-refractive-index anti-glare particles: The organic particle dispersion from step A1, the dispersion of silicon carbide quantum dots grafted with silane coupling agent in ethyl acetate from step A2, and azobisisobutyronitrile were thoroughly mixed and reacted under nitrogen protection at a temperature of 50℃~80℃ to obtain modified high-refractive-index anti-glare particles.
[0011] As a further improvement of this application, the anti-glare coating liquid is prepared by the following steps: thoroughly mixing the first main resin, modified high-refractive-index anti-glare particles, the first photoinitiator, the first organic solvent, and the first additive to obtain the anti-glare coating liquid.
[0012] To achieve the above objectives, this application also provides an optical film, comprising a transparent substrate, a first coating layer, and a second coating layer stacked together, wherein the first coating layer is prepared from the anti-glare coating liquid described above.
[0013] As a further improvement of this application, the first coating has a refractive index of 1.65 to 1.9 and a thickness of 3 μm to 5 μm, and the second coating has a refractive index of 1.4 to 1.6 and a thickness of 100 nm to 135 nm.
[0014] As a further improvement of this application, the material of the transparent substrate is selected from any one of cellulose esters, polyesters, poly(meth)acrylates, and polycarbonates.
[0015] The specific beneficial effects of this application are as follows: In the anti-glare coating liquid and optical film technology solution provided in this application, the modified high-refractive-index anti-glare particles contained in the anti-glare coating liquid are the core advantage. These particles are composed of organic particles grafted with silicon carbide quantum dots using a silane coupling agent. The silane coupling agent ensures the stable bonding between silicon carbide quantum dots and organic particles, preventing particle aggregation and enhancing the overall refractive index of the coating by utilizing the high refractive index characteristics (2.5-2.6) of silicon carbide quantum dots. After the anti-glare coating liquid is prepared into a coating, the organic particles are uniformly distributed within the coating to form a micro-rough structure. Combined with a suitable thickness of 3-5 μm, it can efficiently scatter incident light, achieving an anti-glare level of up to LV6. Even in strong light environments, it can avoid glare problems caused by direct sunlight, ensuring clear and visible display images and providing users with a good visual experience.
[0016] Meanwhile, when the coating prepared by this anti-glare coating liquid (refractive index 1.65-1.9) is used in conjunction with a low-refractive-index coating (refractive index 1.4-1.6, thickness 100-135nm), the two form a reasonable refractive index difference. Unlike traditional technologies, there is no need to add hollow particles to the low-refractive-index coating to reduce the refractive index, which satisfies the condition of destructive interference of light. This reduces the reflectivity of the optical film to below 1%, effectively reducing the interference of ambient light reflection on the display effect. Furthermore, because the low-refractive-index coating does not require the addition of hollow particles, the coating structure is more compact. Combined with the stable structure of the anti-glare coating, this significantly improves the overall hardness (pencil hardness of 5H and above) and abrasion resistance (no scratches in steel wool scratch test). At the same time, the total haze of the coating can be controlled below 2%, balancing excellent optical and mechanical properties to meet the stringent requirements of small-size displays, touch displays, and other applications for optical films. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the structure of the optical film of this application.
[0018] In the figure: 1. Transparent substrate; 2. First coating layer; 3. Second coating layer. Detailed Implementation
[0019] The present application will now be described in detail with reference to the embodiments shown in the accompanying drawings. However, these embodiments do not limit the present application, and any structural, methodological, or functional modifications made by those skilled in the art based on these embodiments are included within the scope of protection of this application.
[0020] To resolve the contradiction between the optical and mechanical properties of optical films, this application provides an anti-glare coating liquid, comprising, by weight, 30 to 70 parts of a first main resin, 0.05 to 1 part of modified high-refractive-index anti-glare particles, 0.5 to 4 parts of a first photoinitiator, 30 to 70 parts of a first organic solvent, and 1 to 10 parts of a first auxiliary agent. The modified high-refractive-index anti-glare particles include organic particles with silicon carbide quantum dots grafted onto a silane coupling agent. The organic particles are polystyrene resin particles, poly(meth)acrylate resin particles, or poly(meth)acrylate-copoly-styrene copolymer resin particles.
[0021] Based on the above technical solution, from the perspective of the function and reaction principle of each component, the first main resin is the matrix skeleton of the coating. It can undergo ultraviolet light curing crosslinking reaction under the action of the first photoinitiator to form a three-dimensional network structure, providing basic mechanical support and adhesion for the coating, ensuring that the coating can be tightly bonded to the surface of the optical substrate. At the same time, its own resin properties also lay the foundation for the light transmittance of the coating. Modified high-refractive-index anti-glare particles are the core functional components. Among them, organic particles (polystyrene, poly(meth)acrylate, or their copolymer particles) can form a micro-rough structure in the coating, which will cause diffuse reflection when light shines on it, thereby achieving the anti-glare effect. The silicon carbide quantum dots (refractive index 2.5-2.6) attached to the surface of the organic particles and grafted with silane coupling agent solve the compatibility problem between quantum dots and organic resin matrix by means of the "inorganic-coupling agent-organic" bridge structure of silane coupling agent, achieving uniform dispersion. On the other hand, it utilizes its high refractive index... The refractive index characteristics significantly increase the refractive index of the entire first coating to 1.65–1.9, facilitating the formation of a refractive index difference with the second coating (refractive index 1.4–1.6) and providing crucial support for satisfying the destructive interference condition of light. The first photoinitiator decomposes under ultraviolet light to generate free radicals, initiating the polymerization and cross-linking reaction of the first main resin, promoting rapid curing and forming of the coating, ensuring the stability of the coating structure and production efficiency. The first organic solvent can dissolve the first main resin, the first photoinitiator, and the first additives, reducing the viscosity of the coating liquid and ensuring uniform coating thickness and absence of bubbles or defects during the coating process. It can be removed by evaporation without affecting the final performance of the coating. Among the first additives (such as dispersants and leveling agents), the dispersant can further assist in the uniform dispersion of modified high-refractive-index anti-glare particles in the system, avoiding particle agglomeration that leads to abnormal haze, while the leveling agent can improve the wettability of the coating liquid on the substrate surface, reduce coating marks, and improve the surface smoothness and optical consistency of the coating.
[0022] The coating liquid of this application, after subsequent coating, drying, and UV curing, can form a first coating layer (high-refractive-index anti-glare layer). Combined with a second coating layer that does not contain hollow particles, it can achieve excellent anti-glare performance (anti-glare level up to LV6) through the micro-rough structure of the particles. It can also achieve light interference cancellation by utilizing the refractive index difference between the first and second coating layers, reducing the reflectivity of the optical film to below 1%. At the same time, because the modified particles are uniformly dispersed and there are no structural defects introduced by hollow particles, the total haze of the coating can be controlled below 2%, maintaining a high level of light transmittance and gloss. It also lays the foundation for the subsequent second coating layer (dense structure) to improve the overall hardness of the optical film (pencil hardness of 4H and above) and scratch resistance (no scratches in steel wool scratch test). Ultimately, it solves the contradiction between the optical performance and mechanical performance of traditional optical films, meeting the needs of small-sized displays, touch displays, etc. for anti-glare, low-reflection, and high-hardness optical films.
[0023] In an optional embodiment, the first primary resin includes acrylate monomers, acrylate homopolymers, methacrylate monomers, methacrylate homopolymers, and copolymers of acrylates and methacrylates.
[0024] In an optional embodiment, the first photoinitiator is selected from at least one of 1-hydroxycyclohexylphenyl ketone, benzyl dimethyl ketal, hydroxydimethyl acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin butyl ether.
[0025] In an optional embodiment, the first organic solvent is selected from at least one of lower alcohols, acetates, ketones, cellosol, dimethylformamide, tetrahydrofuran, propylene glycol monomethyl ether, toluene, and xylene having 1 to 6 carbon atoms. Further, the lower alcohol may be, but is not limited to, methanol, ethanol, isopropanol, butanol, isobutanol, diacetone alcohol, etc.; the acetate may be, but is not limited to, methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, acetic acid cellosol, etc.; and the ketone may be, but is not limited to, methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, acetone, etc.
[0026] In an optional embodiment, the first additive is selected from at least one of dispersants, leveling agents, wetting agents, defoamers, antistatic agents, and leveling agents.
[0027] In an optional embodiment, the modified high-refractive-index anti-glare particles are prepared by the following steps: A1. Preprocessing: Pretreatment of silicon carbide quantum dots: Add silicon carbide quantum dots to a 30% concentrated nitric acid solution, mix thoroughly, and react at 50℃~100℃ for 1h~2h. Wash until neutral, and dry to obtain hydroxylated silicon carbide quantum dots. Preferably, the mass-to-volume ratio of silicon carbide quantum dots to 30% concentrated nitric acid solution is 3g / L~25g / L. For example, 0.3~0.7g of silicon carbide quantum dots can be added to 40~80mL of 30% concentrated nitric acid solution, sonicated for 30 minutes (300W), bathed in a 50~100℃ water bath for 1~2 hours, washed until neutral, and vacuum dried at 60℃ for 4 hours to obtain hydroxylated silicon carbide quantum dots. Organic particle pretreatment: Organic particles are added to ethyl acetate, mixed thoroughly, and then toluene is added. The mixture is then thoroughly mixed again to obtain an organic particle dispersion. Preferably, 2g of organic particles are added to 80-150mL of ethyl acetate, sonicated for 20 minutes (200W), and then 0.05-0.2g of toluene is added and stirred for 10-30 minutes to obtain the organic particle dispersion. The organic particles are polystyrene resin particles, poly(meth)acrylate resin particles, or poly(meth)acrylate-copoly-styrene copolymer resin particles. The mass-to-volume ratio of organic particles to ethyl acetate is 13g / L-40g / L, and the mass ratio of organic particles to toluene is 10:1-40:1.
[0028] In the aforementioned organic particle pretreatment process, ethyl acetate, as a moderately polar primary dispersion medium, plays a crucial role in basic dispersion and slight optimization of particle surface states. Its polarity is highly compatible with the weakly polar structure of organic particles, effectively weakening van der Waals forces between them. With the aid of ultrasonic treatment, it uniformly disperses organic particles in the ethyl acetate system to form a suspension. Simultaneously, it can slightly penetrate the polymer chain gaps on the surface of organic resin particles, causing slight stretching of surface chains and further reducing particle aggregation. Toluene, as a non-polar co-dispersant, although added in low amounts, precisely compensates for the shortcomings of ethyl acetate as a single medium—on the one hand… Its non-polar properties can form hydrophobic interactions with the non-polar groups of the resin side chains, "encapsulating" the surface of organic particles to balance the polarity of the system and adapt to the microenvironment of the organic particle surface. On the other hand, during subsequent stirring, toluene can be uniformly distributed in the system and form a thin non-polar solvent film on the surface of the organic particles. By increasing the steric hindrance and repulsive force between particles, it effectively inhibits the secondary aggregation of organic particles when they stand after ultrasonic dispersion, ensuring that the dispersion remains stable during the "standby" period. The two work together, one as the main component and the other as an auxiliary component. The former achieves basic uniform dispersion of organic particles, while the latter optimizes the long-term stability of the dispersion system, jointly ensuring the uniformity and usability of the organic particle dispersion.
[0029] A2. Coupling agent grafting: Dissolve the silane coupling agent in anhydrous ethanol, add acetic acid, stir thoroughly, then add the hydroxylated silicon carbide quantum dots obtained in step A1, stir thoroughly, wash with ethanol by centrifugation, and disperse in ethyl acetate to obtain a dispersion of silane coupling agent-grafted silicon carbide quantum dots in ethyl acetate; preferably, dissolve 0.05~0.2g of silane coupling agent in 40~80mL of anhydrous ethanol, add 3~7 drops of acetic acid, stir for 10~30 minutes, then add the hydroxylated silicon carbide quantum dots from step A1, sonicate for 10~20 minutes, stir at 40~60℃ for 1~2 hours, wash with ethanol by centrifugation 3~5 times, and disperse in ethyl acetate to obtain a dispersion of silane coupling agent-grafted silicon carbide quantum dots in ethyl acetate.
[0030] A3. Preparation of modified high-refractive-index anti-glare particles: The organic particle dispersion from step A1, the dispersion of silicon carbide quantum dots grafted with silane coupling agent in ethyl acetate from step A2, and azobisisobutyronitrile are thoroughly mixed and reacted under nitrogen protection at a temperature of 50°C to 80°C to obtain modified high-refractive-index anti-glare particles. Preferably, the reaction time is 2 to 4 hours.
[0031] In an optional embodiment, the silane coupling agent in step A2 may be, but is not limited to, at least one of aminosilane (KH-550), epoxysilane (KH-560), methacryloxysilane (KH-570), mercaptosilane (KH-590), vinylsilane (A-151), and alkylsilane.
[0032] In an optional embodiment, the anti-glare coating liquid is prepared by the following steps: thoroughly mixing a first main resin, modified high-refractive-index anti-glare particles, a first photoinitiator, a first organic solvent, and a first auxiliary agent to obtain the anti-glare coating liquid.
[0033] To achieve the above objectives, this application also provides an optical film, comprising a transparent substrate 1, a first coating layer 2, and a second coating layer 3 stacked together, wherein the first coating layer 2 is prepared from the anti-glare coating liquid described above.
[0034] In an optional embodiment, the first coating 2 has a refractive index of 1.65 to 1.9 and a thickness of 3 μm to 5 μm, and the second coating 3 has a refractive index of 1.4 to 1.6 and a thickness of 100 nm to 135 nm.
[0035] Based on the above technical solution, the optical film of this application has several outstanding beneficial effects: Supported by a transparent substrate, the first coating 2 is made of an anti-glare coating liquid containing modified high-refractive-index anti-glare particles, with a refractive index of 1.65–1.9 and a thickness of 3–5 μm. Its high refractive index characteristic forms a reasonable refractive index difference with the second coating 3 (refractive index 1.4–1.6, thickness 100 nm–135 nm), satisfying the condition for destructive interference of incident light, reducing the reflectivity of the optical film to below 1%, and achieving excellent anti-reflection effect. The modified high-refractive-index anti-glare particles in the first coating 1 can form a micro-rough structure, combined with an appropriate thickness, which can efficiently scatter light, achieving an anti-glare level of LV6, ensuring good anti-glare performance; the second coating 3 does not contain hollow particles and is a dense resin layer. Combined with the structural characteristics of the first coating, the surface hardness of the optical film reaches 4H or higher, and no scratches are found in the steel wool scratch resistance test, significantly improving scratch resistance and durability. Meanwhile, this structural design can control the total haze to below 2%, and while ensuring low reflection and anti-glare effects, it maintains high light transmittance and gloss, solving the problem that traditional optical films cannot balance optical and mechanical properties, and meeting the functional requirements of small-sized displays and touch displays for optical films.
[0036] In an optional embodiment, the transparent substrate 1 comprises a light-transmitting substrate that exhibits light transmittance to at least visible light. The material of the transparent substrate 1 is selected from any one of cellulose esters, polyesters, poly(meth)acrylates, and polycarbonates. Preferably, the polyester can be, but is not limited to, polyethylene terephthalate (PET), polyethylene such as ethylene vinyl acetate (EVA), cyclic olefin polymers (COP), cyclic olefin copolymers (COC), polyacrylates (PAC), polycarbonate (PC), polyethylene (PE), polymethyl methacrylate (PMMA), polyetheretherketone (PEEK), polyethylene naphthalate (PEN), polyetherimide (PEI), polyimide (PI), triacetyl cellulose (TAC), methyl methacrylate (MMA), and fluoropolymers.
[0037] In an optional embodiment, the second coating 3 is prepared from a second coating liquid, which, by weight, comprises 0.1 to 3 parts of a second main resin, 0.01 to 0.1 parts of a second photoinitiator, 0.05 to 0.4 parts of a fluorine compound, 85 to 99 parts of a second organic solvent, and a second auxiliary agent.
[0038] In an optional embodiment, the second primary resin is selected from any one of the reaction products of pentaerythritol and acrylic acid, styrene monomer, and oligomer; the fluorinated compound contains at least one photoreactive functional group or is substituted by at least one photoreactive functional group, wherein the photoreactive functional group refers to a functional group that can participate in the polymerization reaction after being irradiated by irradiation light (e.g., visible light or ultraviolet light); the second photoinitiator is selected from at least one of 1-hydroxycyclohexylphenyl ketone, benzyl dimethyl ketal, hydroxydimethyl acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin butyl ether; the second auxiliary agent is selected from at least one of dispersant, leveling agent, wetting agent, defoamer, and antistatic agent.
[0039] In an optional embodiment, the second organic solvent is selected from at least one of alcohols, ketones, aromatic hydrocarbons, amides, esters, and ethers. Preferably, the alcohol can be selected from methanol, isopropanol, ethylene glycol, and butanol, etc.; the ketone can be selected from methyl ethyl ketone and methyl isobutyl ketone, etc.; the aromatic hydrocarbon can be selected from toluene and xylene, etc.; the amide can be selected from dimethylformamide, dimethylacetamide, and N-methylpyrrolidone, etc.; the ester can be selected from ethyl acetate, butyl acetate, γ-butyrolactone, etc.; and the ether can be selected from tetrahydrofuran and 1,4-diane, etc.
[0040] In an optional embodiment, this application also provides a method for preparing a second coating liquid, comprising the following steps: thoroughly mixing 0.1 to 3 parts of a second main resin, 0.01 to 0.1 parts of a second photoinitiator, 0.05 to 0.4 parts of a fluorine compound, 85 to 99 parts of a second organic solvent, and 1 to 3 parts of a second auxiliary agent, and stirring evenly to obtain the second coating liquid.
[0041] To achieve the above objectives, this application also provides a method for preparing the aforementioned optical film, comprising the following steps: The above-mentioned anti-glare coating liquid is applied to the transparent substrate 1, dried at 70~100℃ for 0.5~2 minutes, and then subjected to nitrogen purging with 100~200mJ / cm 2 The first coating 2 was prepared by curing under ultraviolet light. The second coating solution described above is applied to the first coating layer 2, dried at 70~100℃ for 0.5~2 minutes, and then subjected to nitrogen purging with 100~200mJ / cm⁻¹. 2 The second coating 3 was prepared by curing under ultraviolet light.
[0042] In optional implementations, the coating method can be any one of bar coating, knife coating, roller coating, blade coating, die coating, gravure coating, comma coating, slot die coating, lip coating, solution casting, etc.
[0043] To understand the excellent anti-reflective, anti-glare, and scratch-resistant functions of the technical solution of this application, the following embodiments are also provided.
[0044] Example 1 Step 1: Preparation of modified high-refractive-index anti-glare particles S1: Preprocessing Pretreatment of silicon carbide quantum dots: 1g of silicon carbide quantum dots stored in toluene were added to 100mL of 30% concentrated nitric acid solution, sonicated for 30 minutes (300W), bathed in a 70℃ water bath for 1.5 hours, washed until neutral, and dried under vacuum at 60℃ for 4 hours to obtain hydroxylated silicon carbide quantum dots.
[0045] Organic particle pretreatment: Add 4g of poly(meth)acrylate resin particles to 100mL of ethyl acetate, sonicate for 20 minutes (200W), add 0.2g of toluene and stir for 10 minutes (disperse for later use) to obtain an organic particle dispersion.
[0046] S2: Coupling agent grafting Dissolve 0.2 g KH570 in 50 mL of anhydrous ethanol, add 5 drops of acetic acid, stir for 20 minutes, then add hydroxylated silicon carbide quantum dots, sonicate for 15 minutes, stir at 55 °C for 1.5 hours, centrifuge and wash 3 times with ethanol, disperse in ethyl acetate to obtain a dispersion of KH570-grafted silicon carbide quantum dots in ethyl acetate.
[0047] S3: Preparation of modified high-refractive-index anti-glare particles: The organic particle dispersion from step S1, the KH570-grafted silicon carbide quantum dot dispersion in ethyl acetate from step S2, and 0.1 g of azobisisobutyronitrile were thoroughly mixed and stirred at 65°C under nitrogen protection for 3 hours to obtain modified high-refractive-index anti-glare particles.
[0048] Step 2: Preparation of anti-glare coating liquid Mix 48g of methacrylate homopolymer, 0.15g of modified high-refractive-index anti-glare particles, 4.3g of leveling agent (first auxiliary agent), 1.7g of first photoinitiator, 25g of toluene, and 13g of butanone solvent at 1800 rpm for 35 minutes to obtain the anti-glare coating liquid.
[0049] Step 3: Prepare the second coating solution The reaction product of 1g pentaerythritol and acrylic acid, 0.01g of the second photoinitiator, 0.32g of fluorine compound, 92g of the second solvent, and 1.4g of silica sol (second auxiliary agent) were stirred at 1200rpm for 35min to obtain the second coating solution.
[0050] Step 4: Preparation of optical film The anti-glare coating solution from step two above was applied to an 80 μm thick PET transparent substrate using an RDS filament-wound coating rod. It was dried at 90°C for 1 minute and then subjected to nitrogen purging with 180 mJ / cm² gas. 2 The first coating is prepared by curing under ultraviolet light.
[0051] The second coating solution from step three was applied onto the first coating layer using an OSP extrusion coating bar and dried at 90°C for 1.5 minutes. Then, it was purged with nitrogen at 180 mJ / cm². 2 The second coating is prepared by curing under ultraviolet light, and then an optical film is prepared.
[0052] The first coating contains modified high-refractive-index anti-glare particles with a refractive index of 1.78 and a thickness of 4 μm after curing. The second coating has a refractive index of 1.48 and a thickness of 117 nm after curing.
[0053] Example 2 The difference between this embodiment and Embodiment 1 is that the transparent substrate used is made of PMMA.
[0054] Example 3 The difference between this embodiment and Embodiment 1 is that the organic particles selected in step one are poly(meth)acrylate-copoly-styrene copolymer resin particles.
[0055] Comparative Example 1 The difference between this comparative example and Example 1 is that the silicon carbide quantum dots were directly grafted with coupling agents without pretreatment.
[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that the silicon carbide quantum dots are pretreated without being grafted with a coupling agent, and modified high-refractive-index anti-glare particles are directly prepared.
[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that organic particles are directly used as modified high-refractive-index anti-glare particles.
[0058] Comparative Example 4 The difference between this comparative example and comparative example 3 is that 2.8g of hollow silica particles were added to the second coating solution.
[0059] Comparative Example 5 The difference between this comparative example and Example 1 is that no silicon carbide quantum dots are added to the prepared modified high-refractive-index anti-glare particles.
[0060] The optical films prepared in Examples 1-3 and Comparative Examples 1-5 were also subjected to performance tests, and the specific data are shown in Table 1.
[0061] Table 1
[0062] As shown in Table 1, the optical films prepared according to the schemes described in Examples 1-3 have a reflectivity of less than 1% and a haze of less than 2%, exhibiting good anti-glare properties. The adhesion between the first and second coating layers meets the upper limit of industry standards, and the pencil hardness reaches 5H. The second coating surface is smooth, with no hollow particles on the surface or inside, greatly improving the hardness and abrasion resistance of the optical film. It also has a high gloss, ensuring both low reflectivity and anti-glare while maintaining a good appearance. Different transparent substrates have little impact on the defined coating performance, with no significant differences.
[0063] Comparative Example 1 The optical film in this comparative example exhibits poor anti-reflection performance, a low refractive index in the first coating, poor pencil hardness, high haze, mediocre anti-glare properties, and low gloss. This is because the silicon carbide quantum dots are not hydroxylated, lacking active -OH groups on their surface, making it impossible for coupling agents to be effectively grafted. Furthermore, unhydroxylated silicon carbide quantum dots tend to disperse unevenly in the anti-glare coating solution, resulting in localized uneven haze and refractive index distribution. The optical film's haze increases sharply, giving it a white, foggy appearance, and its anti-glare performance is only average.
[0064] Comparative Example 2 The optical film in this comparative example exhibits poor anti-reflection performance, a low refractive index in the first coating, poor pencil hardness, extreme haze, mediocre anti-glare properties, and extremely low gloss. Uncoupled silicon carbide quantum dots, due to their extremely high interfacial energy, violently aggregate into large clusters to reduce surface energy. When preparing the anti-glare coating solution, these clusters cannot be uniformly dispersed, forming precipitates or clumps. These clusters cause uneven light scattering, resulting in a hazy, white appearance, and the silicon carbide quantum dots cannot be uniformly dispersed to increase the refractive index. Numerous tiny air pores exist at the interface between the clusters and the first main resin, leading to an overall low refractive index in the first coating. The clusters also cause numerous visible defects such as particles, white spots, and streaks, resulting in extremely weak pencil hardness, poor abrasion resistance, and extremely low gloss.
[0065] Comparative Example 3 The optical film in this comparative example has high reflectivity and only moderate anti-glare performance. The first coating, which replaces the modified high-refractive-index anti-glare particles with organic particles, has no required difference in refractive index compared to the second coating, resulting in no low-reflection effect. The unmodified organic particles have a lower surface area and therefore lower diffuse reflection compared to the modified high-refractive-index anti-glare particles. Furthermore, the absence of inorganic nanoparticles worsens particle dispersion, thus resulting in only moderate anti-glare performance.
[0066] Comparative Example 4 The optical film in this comparative example has poor pencil hardness and scratch resistance. While the addition of hollow silica particles to the second coating solution reduces the refractive index of the second coating, the presence of these particles significantly decreases the coating's hardness and scratch resistance. The pencil hardness only reaches H, and its abrasion resistance is poor.
[0067] Comparative Example 5 The optical film in this comparative example has poor anti-glare performance. The first coating does not contain large-diameter organic particles, has a low surface area and low degree of diffuse reflection, thus resulting in poor anti-glare performance.
[0068] Refractive index testing method: The refractive indices of the transparent substrate, first coating, and second coating, etc., contained in the optical film, were measured using an ellipsometer while the film was coated on a wafer. More specifically, the refractive indices of the transparent substrate, first coating, and second coating were measured by the following method: each composition was applied to a 3 cm × 3 cm wafer, coated using a spin coater (coating conditions: 1500 rpm, 30 seconds), dried at 90°C for 2 minutes, and then purged with nitrogen at 180 mJ / cm². 2 Under certain conditions, the material is irradiated with ultraviolet light. As a result, coating layers with a thickness of 100 nm are formed.
[0069] The ellipticity of the coating in the wavelength range of 380 nm to 1000 nm was measured using a JAWoollam Co.M-2000 instrument at an incident angle of 70°. The measured ellipticity data (Ψ, Δ) were fitted to the Cauchy model of General Equation 1 below using Complete EASE software, such that the MSE becomes 3 or less.
[0070] Where n(λ) is the refractive index at wavelengths of λ (300nm to 1800nm), and A, B, and C are Cauchy parameters.
[0071] Meanwhile, the refractive index of the transparent substrate and each fine particle is based on information provided in commercially available products.
[0072] Reflectance testing method: The reflectance was measured using a SolidSpec 3700 manufactured by SHIMADZU as the average reflectance.
[0073] Specifically, black tape (vinyl tape 472Black, manufactured by 3M) was attached to the surface of the optical film without a coating to prevent light from entering. After fixing the measurement conditions with a sampling interval of 1 mm, a time constant of 0.1 seconds, a slit width of 20 nm, and a medium scan speed, the optical film was illuminated with light of wavelengths from 380 nm to 780 nm using the 100T mode. The reflectivity was then measured.
[0074] Anti-glare measurement method: A black acrylic plate was attached to the reverse side of the sample coating. A fluorescent lamp from an LED light source was shone onto the surface of the optical film, and the blurring effect of the reflected fluorescent light was evaluated. LV5-6: The outline of the fluorescent lamp is completely uniformly blurred, with good anti-glare performance; LV3-4: Fluorescent lights are blurry but retain their outlines; anti-glare performance is average. LV1-2: The outline of the fluorescent lamp can be clearly seen, or it may be uneven and blurry, with poor anti-glare performance.
[0075] Adhesion measurement method: Use a cross-cut tape cutter to gently score 100 squares on the coating. Then, use 3M 600 tape to press and flatten it onto the scored areas. After 5 minutes, remove the tape and observe the coating loss within the cross-cut area with a magnifying glass. Judge the coating loss by the percentage of coating remaining: 0% if the coating has completely fallen off, and 100% if the coating has completely remained.
[0076] Thickness measurement method: The thickness of the coating was measured using a micrometer (Mitutoyo). The thickness of the coating was calculated by subtracting the thickness of the optical film before coating from the overall thickness after UV curing and drying.
[0077] Measurement methods for total haze value / internal haze value / external haze value: A 4cm × 4cm optical film sample was prepared. The total haze value was calculated by taking three measurements using a haze meter (HM-150, A light source, Murakami Color Research Laboratory). During the measurements, transmittance was measured according to JIS K 7361, and haze value was measured according to JIS K 7105. When measuring the internal haze value, an adhesive film with a total haze value of 0 was bonded to the coated surface of the optical film to be measured to smooth surface irregularities, and the internal haze value was measured in the same manner as the total haze value.
[0078] The external haze value is calculated as the average of the values obtained by calculating the difference between the total haze value and the measured internal haze value.
[0079] Measurement method for 60° gloss value and its deviation: The 60° gloss value was measured using a micro-TRI gloss meter manufactured by BYK Gardner Co., Ltd. During measurement, black tape (3M) was attached to the surface of a transparent substrate without a coating to prevent light from entering. The 60° gloss value was measured by changing the incident angle of light to 60°, and the average of five or more measurements was calculated as the gloss value.
[0080] The deviation of the 60-degree gloss value is calculated by measuring the gloss value 10 times using the above method and calculating the deviation from the data.
[0081] Pencil hardness measurement method: The hardness of the pencils was evaluated using Mitsubishi UNI Hi-UNI series pencils from Japan. Here, the pencil hardness tester was applied three times under a 500g load to the second outermost coating of the optical film, and the highest hardness was measured assuming no scratches were observed.
[0082] Abrasion resistance: The prepared optical film was mounted face up on a friction testing machine. Steel wool (#0000) was applied to the outermost second coating of the optical film 400 times under a 500g load, and the number of scratches formed was calculated. The scratch resistance was evaluated as follows: no scratches meant OK, and scratches meant NG.
[0083] It should be noted that the above description is only for explaining the preferred embodiments of this application and is not intended to limit this application in any way. Therefore, any modifications or changes made to this application under the same inventive spirit should still be included within the scope of protection intended by this application.
Claims
1. An anti-glare coating liquid, characterized in that, The product comprises, by weight, 30 to 70 parts of a first main resin, 0.05 to 1 part of modified high-refractive-index anti-glare particles, 0.5 to 4 parts of a first photoinitiator, 30 to 70 parts of a first organic solvent, and 1 to 10 parts of the first claim. The modified high-refractive-index anti-glare particles include organic particles with silicon carbide quantum dots grafted onto a silane coupling agent. The organic particles are polystyrene resin particles, poly(meth)acrylate resin particles, or poly(meth)acrylate-copoly-styrene copolymer resin particles.
2. The anti-glare coating liquid according to claim 1, characterized in that, The primary resin includes acrylates, methacrylates, and their copolymers or homopolymers.
3. The anti-glare coating liquid according to claim 1, characterized in that, The first photoinitiator is selected from at least one of 1-hydroxycyclohexylphenyl ketone, benzyl dimethyl ketal, hydroxydimethyl acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin butyl ether.
4. The anti-glare coating liquid according to claim 1, characterized in that, The first organic solvent is selected from at least one of lower alcohols having 1 to 6 carbon atoms, acetates, ketones, cellosolves, dimethylformamide, tetrahydrofuran, propylene glycol monomethyl ether, toluene, and xylene.
5. The anti-glare coating liquid according to claim 1, characterized in that, The first additive is selected from at least one of dispersants, leveling agents, wetting agents, defoamers, antistatic agents, and leveling agents.
6. The anti-glare coating liquid according to claim 1, characterized in that, The modified high-refractive-index anti-glare particles are prepared by the following steps: A1. Preprocessing: Pretreatment of silicon carbide quantum dots: Add silicon carbide quantum dots to 30% concentrated nitric acid solution, mix thoroughly and evenly, then react at 50℃~100℃ for 1h~2h, wash until neutral, and dry to obtain hydroxylated silicon carbide quantum dots; Organic particle pretreatment: Add organic particles to ethyl acetate, mix thoroughly, then add toluene, mix thoroughly again to obtain an organic particle dispersion; A2. Coupling agent grafting: The silane coupling agent was dissolved in anhydrous ethanol, acetic acid was added, and after stirring thoroughly, the hydroxylated silicon carbide quantum dots obtained in step A1 were added. After stirring thoroughly and reacting, the mixture was washed by centrifugation with ethanol and dispersed in ethyl acetate to obtain a dispersion of silane coupling agent-grafted silicon carbide quantum dots in ethyl acetate. A3. Preparation of modified high-refractive-index anti-glare particles: The organic particle dispersion from step A1, the dispersion of silicon carbide quantum dots grafted with silane coupling agent in ethyl acetate from step A2, and azobisisobutyronitrile were thoroughly mixed and reacted under nitrogen protection at a temperature of 50℃~80℃ to obtain modified high-refractive-index anti-glare particles.
7. The anti-glare coating liquid according to any one of claims 1-6, characterized in that, The anti-glare coating liquid is prepared by the following steps: thoroughly mixing the first main resin, modified high-refractive-index anti-glare particles, the first photoinitiator, the first organic solvent, and the first auxiliary agent to obtain the anti-glare coating liquid.
8. An optical film, characterized in that, It includes a transparent substrate, a first coating, and a second coating layered together, wherein the first coating is prepared from the anti-glare coating liquid according to any one of claims 1-7.
9. The optical film according to claim 8, characterized in that, The first coating has a refractive index of 1.65 to 1.9 and a thickness of 3 μm to 5 μm, while the second coating has a refractive index of 1.4 to 1.6 and a thickness of 100 nm to 135 nm.
10. The optical film according to claim 8, characterized in that, The transparent substrate is made of any one of cellulose esters, polyesters, poly(meth)acrylates, or polycarbonates.